Partial stapedectomy versus stapedotomy: evaluation of functional outcomes - En-nouali, Amine; Aljalil, Abdelfattah; Hanine, Mohammed A.; Darouassi, Youssef Darouassi; Ammar, Haddou (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Surgery is the treatment of choice for otosclerosis, its technical aspects are codified but varied and its functional results are usually excellent. The aim of this study was to compare the audiometric results obtained after partial stapedectomy and stapedotomy. Methods: A retrospective review of records of patients who underwent stapes surgery for otosclerosis at Avicenna Military Hospital in Marrakesh (Morocco) from January 2008 to December 2018 was conducted. Results: Air conduction thresholds before (53.3±9.8 dB) and after (25.1±6.5) partial stapedectomy was statistically significant (p<0.05) and with stapedotomy before (56.4±7.2) and after (33.1±9.5) surgery also statistically significant (p<0.05). However, air conduction thresholds between the two groups was not statistically significant (p=0.592). Preoperative air-bone gap (ABG) in partial stapedectomy cases was 28.7±8.6 dB and postoperative ABG was 5.7 ± 2.6 dB (p<0.05). Preoperative ABG in patients who underwent stapedotomy was 31.2±6.4 dB and postoperative ABG was 7.5±5.2 dB (p<0.05). ABG improvement in each group was statistically significant, but between the two groups it was not statistically significant (p=0.434). A greater ABG closure rate was observed after partial stapedectomy (81.4%) than after stapedotomy (74.4%), but the difference was not statistically significant (p=0.236). Conclusions: We can conclude that both techniques are effective and safe and that the decision of which technique to perform should depend on the experience and comfort level of the surgeon with either technique.